CHURCHES AS A COMMUNITY DEVELOPMENT AGENCY IN NIGERIA_THROUGH THE LENS OF IBESIKPO ASUTAN LOCAL GOVERNMENT AREA, AKWA IBOM - Balogun Michael Adelakun; Iduemre Ochuko (Romanian Journal of Historical Studies)
Church is one of the social and religious institutions that has both the social responsibility to preach and cater for the wellness of individual and communities. The study examined the impacts of churches as the community development agency in Ibesikpo Asutan Local Government of Akwa Ibom state as a lens to the country. It investigated the specific community projects undertaken by the churches in the past nine years in the area; also determined the source of income/finance for developmental project in the area; examined the type of members/worshippers in Ibesikpo Asutan Local Government Area churches; and assessed churches challenges in carrying-out community development projects in the Area. Structural functionalism theory was used for the study. The sample size of seventy (70) interviewees were selected within community and churches leader for in-depth interviewed. The data collected were analyzed, and it was recommended that organizations, individual both in diasporas should emulate the ideals of churches to key into the future of community and left behind legacy for other to trend by strategize both developmental ambitions of the populace. Also, Government should adjust the policy for effective community development especially in rural community by the appointment of committee that comprises individual both within and outside the communities (local, state and federal) to be sure developments get to grassroots. In addition to churches efforts in development of the communities, there is need to establish micro-loan for poverty alleviation and scholarship schemes for the less privileged in these locality as its extended to the country at large